The Sommersdorf mummies: an interdisciplinary investigation on human remains from a 17th-19th century aristocratic crypt in southern Germany - Alterauge, Amelie (PLOS ONE, 2017)
Sommersdorf Castle (Bavaria, Germany) is a medieval castle complex which has been inhabited by the aristocratic family von Crailsheim. The deceased were entombed in a crypt located in the parapets underneath the castle’s church, resulting in mummification of the bodies. Based on the family chronicle and oral history, identities have been ascribed to the mummies. The aim of the study is therefore to test the accuracy of the historical records in comparison to archaeological, anthropological and genetic data. Today, the crypt houses eleven wooden coffins from the 17th to 19th century AD. In ten of these, mummified and scattered human remains were found. Archive records were studied in order to identify names, ancestry, titles, occupation, date of birth and death, and place of interment of the individuals. The coffins were visually inspected and dated by typo-chronology, and the mummified and scattered skeletal remains were subjected to a physical anthropological examination. In total, the crypt contains the remains of a minimum number of nine individuals, among them three adult males, five adult females and one infant. A detailed scientific examination, including prior conservation, ancient DNA analyses, and computed tomography (CT), was performed on five mummies. By means of the CT data age at death, sex, body height, pathologies, and anatomical variants were investigated. CT analysis further showed that the bodies were naturally mummified. Mitochondrial DNA analyses revealed that the tested individuals are not maternally related. In addition, health, living conditions and circumstances of death of the entombed individuals could be highlighted. Being confronted with the strengths, weaknesses and limitations of each methodological approach, probable identification was achieved in two cases.